Defining Rurality in Medicare Administrative Data. Issue 12 (December 2017) - Snyder, John E.; Jensen, Matthew; Nguyen, Nguyen X.; Filice, Clara E.; Joynt, Karen E.
Abstract : Rural beneficiaries make up nearly one quarter of the Medicare population, yet rural providers and patients face specific challenges with health and health care delivery that remain inadequately understood. Health disparities between rural and urban residents are widespread, barriers to health care in rural communities persist, and the rural health care workforce is limited. To better understand and track the relationship between rurality and performance under Medicare's payment programs, researchers must be able to identify rural beneficiaries, providers, and hospitals. Although numerous definitions of rurality are applied across the Medicare program, empirical research is lacking comparing the different definitions of rurality and the impact of their application to quality, outcome, or costs. Definitions that recognize rurality as a graded concept, rather than a dichotomous one, hold promise. Understanding the strengths and limitations of different approaches to identifying rurality will help researchers choose the best method for their particular purpose, and help policymakers interpret studies using these approaches. Abstract : Supplemental Digital Content is available in the text.